Nonepiphyseal Giant Cell Tumor of the Rib: A Case Report. (16th October 2012) - Moschouris, Hippocrates; Marinis, Athanasios; Bouma, Evanthia; Karagiannis, Evangelos; Kiltenis, Michalis; Papadaki, Marina
Abstract : A case of a 32-year-old female patient with a giant cell tumor originating in the middle part of the left 10th rib is presented. On X-rays and CT, the tumor caused a well-defined osteolysis with nonsclerotic borders. On MRI, it exhibited intermediate signal intensity on T1 sequences and central high signal and peripheral intermediate signal on T2 sequences. On contrast-enhanced MR images both central and peripheral-periosteal enhancement was noted. Thanks to its small size (2 × 1.3 cm), the lesion was easily resected en bloc with a part of the affected rib. The patient is free of recurrence for 3 years after the operation.